Evaluating mangroves as nature-based solutions for coastal protection under current and future sea level rise scenarios - Philip-Neri Jayson-Quashigah; Joanna Staneva; Wei Chen; Bughsin’ Djath; Edem Mahu; Kwasi Appeaning Addo (Frontiers in Marine Science, 2025)
Coastal hazards, such as erosion and flooding, pose significant threats to many coastal areas, and in extreme cases, have led to the decimation of some coastal communities. Historically, management has mostly focused on the use of grey infrastructure such as seawalls and groynes. However, these interventions are costly and can cause unintended consequences, promoting a shift toward Nature-based Solutions (NbS), such as the use of mangroves. Mangroves, particularly, have been proven to protect shorelines due to their ability to attenuate waves and trap sediment. However, there is limited research, particularly in data-deficient regions such as Ghana, West Africa, to support such NbS initiatives. This study explored the potential of mangroves as NbS to mitigate coastal erosion, using the 1D morphodynamic model XBeach. The baseline model was validated against measured coastal profiles, and the results show accurate predictions of sediment volume changes with an overall RMSE of 0.75 m. Based on the calibrations, we explored the effects of mature mangroves at varying densities on the berm and within the intertidal zone under current and projected sea level conditions, on coastal erosion. The results show a significant reduction in sediment volume erosion from 28 m 3 to 0.9 m 3 in the current situation, representing 97% protection; and from 468 m 3 to 2.6 m 3 under future sea level rise of 0.233 m by 2040, indicating 99% protection. Notably, high densities of mangroves, introduced on the berm, which is more practical for the area, provided up to 53% reduction in erosion for the current situation and 97% for the future. These scenario-based simulations demonstrate the potential of mangroves as a dynamic coastal defense strategy, with the approach providing a valuable tool for testing and optimizing NbS interventions.

Strengthening Ocean Science Capacity: Insights from the West Africa Marine Science Symposium - Edem Mahu; Julia Luthringer; Kwame Koranteng; Annette Kailey Ankrah (Oceanography, 2025)
West Africa has an extensive coastline stretching 7,367 km over 12 mainland countries and two archipelagos. The region’s coastal and marine ecosystems are among the most productive and biologically diverse in the world. However, the ocean resources are under intense anthropogenic pressures encompassing pollution, habitat degradation, biodiversity loss, overfishing, and climate-change-​induced sea level rise. These challenges call for science-based and community-led actions to reverse current negative trends. Unfortunately, poor capacity to understand West Africa’s ocean is an age-old struggle by scientists in the region, and it remains among the least studied globally.

Perspectives from Developers and Users of the GOA-ON in a Box Kit: A Model for Capacity Sharing in Ocean Sciences - Alexis Valauri-Orton, Valauri-Orton; Kaitlyn Lowder; Kim Currie; Christopher Sabine; Andrew Dickson; Sophie Chu; Alberto Acosta; Francis Asuquo; Rafael Bermudez; Ulrich Bilounga; Kishore Boodhoo; Benjamin Botwe; et al. (Oceanography, 2025)
Providing reliable instrumentation that enables collection of high-​quality, comparable data is one of the most challenging aspects of establishing ocean acidification monitoring programs. This is especially true for under-resourced countries, where such data are mostly unavailable. In 2016, The Ocean Foundation (TOF) worked with international bodies, including the International Atomic Energy Agency’s Ocean Acidification International Coordination Centre and the Global Ocean Acidification Observing Network (GOA-ON), and subject matter experts to develop a set of equipment known as the “GOA-ON in a Box” kit (The Ocean Foundation, 2017). This comprehensive kit provides researchers with everything needed—down to specialized rubber bands—to obtain weather-quality carbonate system measurements as defined by GOA-ON (Newton et al., 2015). Data are generated from spectrophotometric measurements of pHT and manual titrations for total alkalinity from discrete samples as well as in situ sensors, the iSAMI-pH and a CTD. The kit’s modular design, composed of nearly 100 unique items, makes it much less expensive than comparable integrated systems and allows for easier troubleshooting and replacement of supplied spare components.

The Coastal Ocean Environment Summer School In Nigeria and Ghana: The Value of Long-Term, Sustained Capacity Sharing - Brian Arbic; Johnson Adjetey; Andrews Agyekumhene; Mosunmola Akinwunmi; Lailah Akita; Lois Anderson; Joseph Ansong; Kwasi Appeaning Addo; Eunice Asamoah; Olawale Awe; Christian Buckingham; Janae’ Collier; et al. (Oceanography, 2025)
The Coastal Ocean Environment Summer School In Nigeria and Ghana (COESSING; https://coessing.org) has been run for one week every year since 2015. The school, an endorsed project of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030), has provided a platform for approximately 1,000 scientists from Africa, the United States, and Europe to exchange scientific knowledge, to network, to learn, and to collaborate. Our interdisciplinary, multicultural, and multi-institutional approach offers a model for knowledge exchange across the globe and across different educational levels.

Building and Sharing Ocean Sciences Capacity Through Project-Based Learning - Ebenezer Nyadjro; Anthi Oikonomou; Abdulwakil Saba; Edem Mahu; Georgios Vagenas; Joseph Ansong; Paige Martin; Andrews Agyekumhene; Eunice Asamoah; Richmond Kennedy Quarcoo; Janae’ Collier; Lailah Akita (Oceanography, 2025)
The challenges facing the ocean and its resources have become increasingly complex and transboundary, requiring coordinated efforts for effective management and sustainable use. However, this coordination is currently hindered by the uneven distribution of capacity and equipment, particularly in developing regions. This article discusses project-based learning (PBL) as a pathway to transferring and sharing capacity in global ocean sciences. It highlights a successful PBL program, as well as challenges encountered and lessons learned. Addressing these obstacles is crucial for ensuring equity in solving issues that impact the ocean.

The Ocean Foundation’s Ocean Science Equity Initiative: An Example of a Comprehensive, Intentionally Co-Designed Capacity Development Effort - Alexis Valauri-Orton; Brian Arbic; Marcia Creary-Ford; Kaitlyn Lowder; Edem Mahu; Courtnie Park; Katy Soapi; Aileen Tan Shau Hwai (Oceanography, 2025)
The Ocean Foundation’s Ocean Science Equity Initiative—EquiSea—was founded in 2022 to address systemic inequities in ocean science capacity and opportunities. It provides financial support for projects, coordinates capacity development activities, fosters collaboration and co-financing of ocean science, and supports the development of low-cost ocean science technologies. The EquiSea strategic framework was co-developed with input from more than 200 ocean science practitioners in more than 35 countries. The authors of this article are those who played the most active roles in EquiSea’s development.

Quantification and characterization of microplastics ingested by mangrove oysters across West Africa - Edem Mahu; Tyronne Jude Vanderpuye-Orgle; Charles Mario Boateng; Maurice Oti Edusei; Gabriella Akpah Yeboah; Ernest Obeng Chuku; Paulina Okpei; Isaac Okyere; David Dodoo-Arhin; Edward Akinnigbagbe Akintoye (Environmental Science and Pollution Research, 2024)
Microplastic ingestion by marine organisms presents a challenge to both ecosystem functioning and human health. We characterized microplastic abundance, shape, size, and polymer types ingested by the West African mangrove oyster, Crassostrea tulipa (Lamarck, 1819) sampled from estuaries and lagoons from the Gambia, Sierra Leone, Ghana, Benin, and Nigeria using optical microscopy and Fourier transform infrared (FTIR) techniques. A total of 780 microplastics were isolated in the whole tissues of the 250 oysters ( n = 50 oysters per country). The abundance and distribution of microplastics in the oysters followed the pattern: the Gambia > Ghana > Sierra Leone > Nigeria > Benin. The Tanbi wetlands in the Gambia recorded the highest average of 10.50 ± 6.69 per oyster while the Ouidah lagoon in Benin recorded the lowest average of 1.80 ± 1.90 per oyster. Overall, microplastic numbers varied significantly ( p < 0.05) among the five countries. Microfibers, particularly those within 1001–5000 μm size, dominated the total microplastic count with a few fragments and films. No spherical microplastics were isolated in the oysters. In the Sierra Leone and Benin oysters, fragments and films were absent in the samples. Microplastic between the 1001 and 5000 μm size class dominated the counts, followed by 501–1000 μm, 101–500 μm, and 51–100 μm. Five polymer groups namely polyethylene, polyester, nylon, polypropylene, and polyamide were identified across the five countries, with polyethylene occurring in oysters from all five countries and polyester occurring in all but the oysters from Nigeria. This diversity of polymers suggests varied sources of microplastics ingested by the studied oysters. The absence of microspheres across the five supports findings from other studies that they are the least ingested and highly egested by the oysters. Graphical Abstract

Assessment of Ecological Quality Status of Western Nigeria Offshore Waters (Gulf of Guinea) Using Macrobenthic Assemblage - Abiodun Yusuf Sule; Ademola Semiu Yakub; Ayoola Olubunmi Nubi; Bassey Okon Bassey; Edem Mahu; Juliet Kelechi Igbo; Beatrice Omolola Bello; Zacharie Sohou; Olushola Ayoola Abiodun; Oluwabukunola Ayokunmi Olapoju; Esther Osayevbovban Nosazeogie; Musa Abdullahi Izge; et al. (Thalassas: An International Journal of Marine Sciences, 2024)

Impact of agricultural practices on ecosystem health of lagoons: a case study of the Keta Lagoon Complex in Ghana, West Africa - Edem Mahu; Priscilla Danso; Maurice Oti Edusei; Kweku Amoako Atta deGraft-Johnson (Environmental Monitoring and Assessment, 2023)

Human health risk and food safety implications of microplastic consumption by fish from coastal waters of the eastern equatorial Atlantic Ocean - Edem Mahu; Wise Goodluck Datsomor; Regina Folorunsho; Jerome Fisayo; Richard Crane; Robert Marchant; Judith Montford; Mario Charles Boateng; Maurice Edusei Oti; Margret Ngozi Oguguah; Christopher Gordon (Food Control, 2023)

Addressing data gaps in marine litter distribution: Citizen science observation of plastics in coastal ecosystems by high-school students - Ana I. Catarino; Edem Mahu; Marine I. Severin; Lazare Kouame Akpetou; Pavanee Annasawmy; Francis Emile Asuquo; Fiona Beckman; Mostapha Benomar; Annette Jaya-Ram; Mohammed Malouli; Jan Mees; Ivanice Monteiro; et al. (Frontiers in Marine Science, 2023)
The Citizen Observation of Local Litter in coastal ECosysTems (COLLECT) project (2021-2022) is a citizen science initiative, supported by the Partnership for Observation of the Global Ocean (POGO), which aimed to acquire distribution and abundance data of coastal plastic litter in seven countries: in Africa (Benin, Cabo Verde, Côte d’Ivoire, Ghana, Morocco, Nigeria) and Asia (Malaysia). In this paper, we describe the workflow used to establish and run this project, as well as the methodologies to acquire data. The COLLECT project consisted of training local students (15 - 18 years old) from ten second cycle institutions (“high schools”) on sampling and analyzing macro-, meso- and microplastics in beach sediments, using a quantitative assessment protocol. We further describe in detail the methodologies applied in assessing the impact of participating in the activities from a social sciences perspective. All documents and materials resulting from this project will be open access and available according to the FAIR Principles (Findable, Accessible, Interoperable, and Reusable). The results and outcomes from COLLECT will contribute to expanding knowledge and establishing baseline information on coastal plastic pollution, with citizen science being an enabler of open science, allowing data to be freely available to the public, academics and policymakers. Expected results from the use of the COLLECT protocol globally will further contribute to the identification of hotspots of coastal plastic litter, and bring awareness to local communities on the potential consequences of plastic pollution. The COLLECT project actively contributes with data suitable to survey plastic litter to the United Nations’ Sustainable Development Goals (UN SDGs), in particular to SDG 14, on the sustainable use of the ocean.

Climate Resilience and Adaptation in West African Oyster Fisheries: An Expert-Based Assessment of the Vulnerability of the Oyster Crassostrea tulipa to Climate Change - Edem Mahu; Salieu Sanko; Allieubakarr Kamara; Ernest Obeng Chuku; Elizabeth Effah; Zacharie Sohou; Yaovi Zounon; Victoria Akinjogunla; Ruth Oluwatoyin Akinnigbagbe; Hamet Diaw Diadhiou; Robert Marchant (Fishes, 2022)
Globally, over 85% of oyster reefs have been lost, and the combined effects of climate change, ocean acidification, and environmental degradation, including pollution and mangrove overharvesting, could further reduce global oyster fisheries in the coming decades. To understand the level of impact of climate change on the oyster fishery in West Africa, an expert-based vulnerability assessment to climate change was conducted for the West African mangrove oyster (Crassostrea tulipa, Lamarck 1819). Using a combination of the exposure of the oyster to climatic stressors (estuarine temperature, salinity, river flow, surface run-off, sea level rise, and estuarine circulation) together with an assessment of sensitivity to these stressors, we estimate the overall vulnerability of C. tulipa to climate change. A very high overall climate vulnerability score of 12 on a scale of 16 was calculated for C. tulipa. While the overall climate exposure score in the West African coastal region remained high, the high sensitivity of C. tulipa to hydrographic conditions of its habitat, in particular salinity, coupled with its sessile and habitat-specific nature, pushed the overall vulnerability to very high. Early life history settlement requirements, adult mobility, and sensitivity to salinity were the three most important biological and sensitivity attributes that determined the vulnerability score. By leaving each of these three sensitivity attributes out of the analysis, the overall vulnerability score was reduced to 9 (i.e., from very high to high). A negative directional effect of climate change, coupled with a low potential for change in distribution, threatens the C. tulipa fishery in a long-term adverse climate scenario. We recommend management efforts that incorporate climate resilience and adaptation practices to prioritize recruitment success, as well as the development of breeding lines with climate-resilient traits.

Enhancing Satellite Oceanography-Driven Research in West Africa: a Case Study of Capacity Development in an Underserved Region - Ebenezer S. Nyadjro; Brian K. Arbic; Christian E. Buckingham; Paige E. Martin; Edem Mahu; Joseph K. Ansong; Johnson Adjetey; Elvis Nyarko; Kwasi Appeaning Addo (Remote Sensing in Earth Systems Sciences, 2022)

Putting Training into Practice: An Alumni Network Global Monitoring Program - Lilian Krug; Subrata Sarker; Samiul Huda; Adriana Gonzalez-Silvera; Akinnigbagbe Edward; Carla Berghoff; Christian Naranjo; Edem Mahu; Jorge López-Calderón; Luís Escudero; Maria Tapia; Mauricio Noernberg; et al. (Oceanography, 2021)

Correction to: Probabilistic risk assessment and risk mapping of metals in tropical estuarine sediments using the Aquarisk model - Edem Mahu; Elvis Nyarko; Daniel Asiedu; Wahab Sowah Laryea; Ron Szymczak; John Twining (Environmental Monitoring and Assessment, 2018)

Probabilistic risk assessment and risk mapping of metals in tropical estuarine sediments using the 1 quarisk model - Edem Mahu; Elvis Nyarko; Daniel Asiedu; Wahab Sowah Laryea; Ron Szymczak; John Twining (Environmental Monitoring and Assessment, 2018)